DAMPAK VARIETAS YANG BERBEDA TERHADAP HASIL GULA SEMUT BERBAHAN NIRA TEBU - Anna Kusumawati; Andhika Ardiansyah (Institute of Computer Science (IOCS), 2023)
Sugar cane is the main commodity in Indonesia as a raw material for the sugar industry, but it has not yet been developed into other products. Ant sugar is a processed product of sugar cane juice that has a lower glycemic index than regular sugar and has the potential to increase the income of sugarcane farmers. Currently, there is no research that examines the differences in the quality of ant sugar produced from sugarcane with different varieties, so this study aims to analyze the quality of cane sugar produced from three different types of sugarcane, through organoleptic tests so that consumers' tastes can be determined. This study used a non-factorial Completely Randomized Design (CRD) with three varieties of sugarcane namely Bululawang, BZ 194, and PSDK. The results showed that the varieties of sugarcane plants against ant sugar made from sugarcane juice did not have a significant difference in terms of color, aroma, and texture. The results of the taste of ant sugar have a significant difference so the Bululawang variety is the most preferred variety. The differences in sugarcane varieties give different characteristics to the yield of ant sugar based on the quality content of the sap.